MIGHTEE-H i: the H i size-mass relation over the last billion years - Rajohnson, S.H.A.; Frank, B.S.; Ponomare, A.A.; Maddox, N.; Kraan-Korteweg, R.C.; Jarvis, M.J.; Adams, E.A.K.; Oosterloo, T.; Baes, M.; Spekkens, K.; Adams, N.J.; Glowacki, Marcin; et al. (OXFORD UNIV PRESS, 2022)
We present the observed H i size-mass relation of 204 galaxies from the MIGHTEE Survey Early Science data. The high sensitivity of MeerKAT allows us to detect galaxies spanning more than 4 orders of magnitude in H i mass, ranging from dwarf galaxies to massive spirals, and including all morphological types. This is the first time the relation has been explored on a blind homogeneous data set that extends over a previously unexplored redshift range of 0 < z < 0.084, i.e. a period of around one billion years in cosmic time. The sample follows the same tight logarithmic relation derived from previous work, between the diameter (DHI) and the mass (MHI) of H i discs. We measure a slope of 0.501 ± 0.008, an intercept of -3.252+0.073-0.074, and an observed scatter of 0.057 dex. For the first time, we quantify the intrinsic scatter of 0.054 ± 0.003 dex (∼10 percent), which provides a constraint for cosmological simulations of galaxy formation and evolution. We derive the relation as a function of galaxy type and find that their intrinsic scatters and slopes are consistent within the errors. We also calculate the DHI-MHI relation for two redshift bins and do not find any evidence for evolution with redshift. These results suggest that over a period of one billion years in look-back time, galaxy discs have not undergone significant evolution in their gas distribution and mean surface mass density, indicating a lack of dependence on both morphological type and redshift.